Correlation of utrophin levels with the dystrophin protein complex and muscle fibre regeneration in Duchenne and Becker muscular dystrophy muscle biopsies - Janghra, N; Morgan, J; Sewry, C; Wilson, F; Davies, K; Muntoni, F; Tinsley, J (2016)
Abstract Duchenne muscular dystrophy is a severe and currently incurable progressive neuromuscular condition, caused by mutations in the DMD gene that result in the inability to produce dystrophin. Lack of dystrophin leads to loss of muscle fibres and a reduction in muscle mass and function. There is evidence from dystrophin-deficient mouse models that increasing levels of utrophin at the muscle fibre sarcolemma by genetic or pharmacological means significantly reduces the muscular dystrophy pathology. In order to determine the efficacy of utrophin modulators in clinical trials, it is necessary to accurately measure utrophin levels and other biomarkers on a fibre by fibre basis within a biopsy section. Our aim was to develop robust and reproducible staining and imaging protocols to quantify sarcolemmal utrophin levels, sarcolemmal dystrophin complex members and numbers of regenerating fibres within a biopsy section. We quantified sarcolemmal utrophin in mature and regenerating fibres and the percentage of regenerating muscle fibres, in muscle biopsies from Duchenne, the milder Becker muscular dystrophy and controls. Fluorescent immunostaining followed by image analysis was performed to quantify utrophin intensity and β-dystrogylcan and ɣ –sarcoglycan intensity at the sarcolemma. Antibodies to fetal and developmental myosins were used to identify regenerating muscle fibres allowing the accurate calculation of percentage regeneration fibres in the biopsy. Our results indicate that muscle biopsies from Becker muscular dystrophy patients have fewer numbers of regenerating fibres and reduced utrophin intensity compared to muscle biopsies from Duchenne muscular dystrophy patients. Of particular interest, we show for the first time that the percentage of regenerating muscle fibres within the muscle biopsy correlate with the clinical severity of Becker and Duchenne muscular dystrophy patients from whom the biopsy was taken. The ongoing development of these tools to quantify sarcolemmal utrophin and muscle regeneration in muscle biopsies will be invaluable for assessing utrophin modulator activity in future clinical trials.